Pharmacokinetic, pharmacodynamic, and pharmacogenetic assays to monitor clopidogrel therapy - Bhawani Yasassri Alvitigala; Lallindra Viranjan Gooneratne; Godwin Roger Constantine; Rajapaksha Arachchige Namal Kumarasiri Wijesinghe; Liyanage Dona Ashanthi Menuka Arawwawala (Wiley, 2020)
Abstract Clopidogrel is the most common and widely used antiplatelet agent for patients with coronary artery disease following confirmation by electrocardiographic studies. The nonresponsiveness of patients to clopidogrel and the possibility of testing for clopidogrel resistance by platelet function assays (PFA) are contentious issues. Light transmission aggregometry (LTA) is considered as the gold standard test among all PFA. In this review, the most commonly used PFA used for monitoring the effect of clopidogrel, LTA, vasodilator‐stimulated phosphoprotein assay phosphorylation, rotational thromboelastometry (ROTEM) delta and ROTEM platelet, thromboelastography, PFA‐100, VerifyNow P2Y12 assay, Multiplate analyzer, Plateletworks assay and pharmacogenetic studies, are comparatively discussed including their principles of action, advantages, and disadvantages. VerifyNow P2Y12 assay can be accepted as the ideal point of care test out of the discussed assays. However, modified assays are required which could overcome the limitations associated with currently available assays.